Strategy Analysis for Increasing Advertisement Tax Revenue in the Era of Digitalization at the Jakarta Regional Revenue Agency - Sari, Ridha Fitri Nurita (Indonesian Scientific Publication, 2023)
The phenomenon of this research is the transition from the use of billboards to digital billboards, resulting in a decrease in billboard tax revenue. Because there are many companies that promote their goods or put up billboards digitally. This study aims to determine what strategies are used by the Regional Revenue Agency to increase advertisement tax revenue in the digitalization era. The research method used is descriptive qualitative research. Sources of data consist of secondary data in the form of interviews and primary data in the form of documentation data. The results of this study indicate: (1) Bapenda and UP3D continue to be more active in terms of providing appeals to taxpayers to report and pay their reclamation tax when due. (2) LED billboards are billboards with a substantial increase in advertisement tax revenue compared to conventional billboards. (3) There are still many potentials that can be subject to advertisement tax to increase advertisement tax revenue. Suggestions in this study are (1) Bapenda should be more active in viewing advertisements that do not have a license but have been published. (2) Must provide more in-depth socialization to taxpayers so that taxpayers continue to report their published reclamation tax. (3) Providing firmer assertiveness or sanctions to taxpayers who do not fulfill their obligations or administrators of illegal advertisements in order to be more deterred?